THE CARRYING CAPACITY AND ENVIRONMENTAL FRIENDLY PLANS FOR FUTURE TOURISM DEVELOPMENT IN RHODES ISLAND, GREECE - Dimitris VANDARAKIS; Kalliopi KYRIAKOU; Fragiska-Karmela GAD; Vassileios KAPSIMALIS; Ioannis PANAGIOTOPOULOS; Vassiliki LOUKAIDI; Georgios-Aggelos HATIRIS; Andreas SIOULAS (European Journal of Geography, 2019)
During the last decades, Greece has been emerged as a popular tourist destination providing high quality tourist services. Diverse landscape, extended sandy beaches, numerous archaeological sites, people’s hospitality, filling of safety, and adequate infrastructure are some factors that have increased the touristic value of Greece. In particular, Rhodes Island, located in the southeastern Aegean Archipelagos, attracts more than two million (2.000.000) non- residents visitors per year that is approximately 10% of the Greek tourist product. The Carrying Capacity Assessment of Rhodes Island aims in finding different, high standards tourist activities, in order to maintain the growth of this sector. The required data (socio-economic and geographical) were analyzed according to the PAP/RAC methodology. In order to reduce the negative effects of tourism, different activities must be provided such as, hiking, biking, divingtourism, archaeological tourism, excursions in the remarkable natural environment.Furthermore, the redefinition of the urban planning will contribute to the decongestion of the tourism concentration along with the environmental decompression, and it will contribute to the sustainable development of the island.